Efeito de aditivos e Fishfertilquitosana® em meios sólidos na produção de conídios de Metarhizium anisopliae (Metsch.) Sorokin e Beauveria bassiana (Bals.) Vuillemin. - Schamne, Priscila Antunes (2010)
Entomopathogenic fungi are increasingly used to control agricultural pests, so it is needed to develop more efficient methods to mass production of these agents. Thus, the objective of this study was evaluate the effect of Fishfertilquitosana® (FQT) on biological parameters of the entomopathogenic fungi Metarhizium anisopliae and Beauveria bassiana, as well as the effect of additives in the production of M. anisopliae and B. bassiana at solid rice medium. The product Fishfertilquitosana® was evaluated at concentrations of 0.025%, 0.05%, 0.1%, 0.2%, 0.4% considering vegetative growth, conidia production and viability. It was also evaluated, conidia production and viability at solid rice medium using different additives: potato broth (5%, 10%: 15%, 20%), lactose (1 g, 2 g, 3 g, 4 g;) yeast extract (0.005 g, 0.01 g, 0.1 g), salts like NaNO3, KCl; CaCl2.2H2O; MgSO4.7H2O and ascorbic acid 0.01 g. In both experiments, data were subjected to analysis of variance and the means were compared by regression and Tukey test (P?0.05). It was found that the increase of the product FQT at the culture medium inhibited the vegetative growth for both fungi, conidia production was inversely proportional to the increase of FQT at the culture medium for M. anisopliae. To B. bassiana at concentration of 0.1% it was observed the highest conidia production (5.32Ã 107 conidia mL- 1 ), the other concentrations reduced the production of this fungus. The addition of the product to the culture medium did not affect the viability of conidia, and M. anisopliae and B. bassiana germinated above 90 and 70% respectively. Increasing the additives concentration at the culture rice medium, it was observed a small decrease at conidia production of both fungi studied, except at the treatment with yeast extract 1 g lactose 0.005 g which there was a production increasing of the fungus M. anisopliae (2.31Ã 108 and 1.89Ã 108 conidia.g?¹, respectively). Viability was not affected by additives at culture medium for both fungi species evaluated. The addition of 0.01 g of KCl increased the production of M. anisopliae and the other treatments did not affect the production of this fungus. For B. bassiana, the addition of mineral salts at the culture medium did not affect their production. Conidial germination of M. anisopliae was not affected by the addition of mineral salts at the culture medium. But for B. bassiana, the treatment with NaNO3 differed statistically from the treatments with MgSO4 and KCl, the other treatments showed no significant differences compared to the control treatment.